Moderasi ‘di atas’ Tekstualisme-Kontekstualisme: Metodologi Pemahaman Sunnah Yusuf al-Qaradhawi - Sansan Ziaul Haq; Asep Salahudin (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The Moderation ‘beyond’ Textualism-Contextualism: Yusuf al-Qaradhawi’s Methodology of Understanding the SunnahThe discourse of understanding the Sunnah of the Prophet—as in the interpretation of the Qur'an—in this contemporary era is faced with a dilemmatic choice between following the global trend or settling for the 'purity' of the islamic teachings. Responding to this problem, some groups approach the textual approach that is oriented to the practice of Islam in the style of al-salaf al-salih strictly, while others advocate the contextualization of Islamic sources creatively according to the dynamics of the times. This paper will specifically discuss the manhaj offered by Yusuf al-Qaradhawi in synthesizing the two approaches in the context of understanding the Sunnah. Through interpretive analysis methods, this article finds that the methodology of understanding the Sunnah initiated by al-Qaradhawi on the one hand is moderate because it seeks to mediate the two 'excessive' sides of the textual and contextual approaches, and at the same time is comprehensive because linking the demand of interpreting the Sunnah to the broader methodological principles.